ANALISIS DAN IMPROVEMENT KUALITAS PRODUK PADA PROSES PRODUKSI BISKUIT MENGGUNAKAN PENDEKATAN DMAIC - Hikmah Hidayati (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
PT. Fast Moving Consumers Goods in order to decrease the number of defects on biscuits dannisa Currant in the method DMAIC (Define, Measures, Analyze, Improvement, Control). The study was conducted to determine the factors that cause the occurrence of color defects are not standard and reduce the number of defects with the methodology DMAIC (Define, Measure, Analyze, Improvement and Control). Based on the analysis of causal diagram (Fishbone diagram) and by using the tools Nominal Group Technique (NGT) found five dominant cause of which is the engine burner is not effective and difficult in setting up the machine, raw material particle size is not standard and nonstandard dough temperature. With the method (5W + 1H) the corrective actions taken are: the addition of 6 units of burner, reduce the particle size of the raw material and the dough temperature settings, and additional man power on the unit before the process is in the process moulder. From the results of improvement, DPMO value has increased very significantly.